Perfil epidemiológico de gestantes com HIV em um município do interior do Amazonas - Paiva, Eliabe Castro de (Brasil, 2024)
To analyze the epidemiological profile of pregnant women with the human immunodeficiency virus (HIV) in the municipality of Coari, Amazonas, from 2018 to 2022. Methods: This is a descriptive, cross-sectional study with a quantitative approach, carried out using data contained in the notification forms of pregnant women with HIV. Data were analyzed using descriptive statistics, using absolute and relative frequencies. Results: Between 2018 and 2022, 2020 had the highest number of notifications of pregnant women with HIV, 100% of pregnant women were brown, the most prevalent age group was 19-27 years, complete high school and living in urban areas. Prenatal care was performed by 95.83% of the pregnant women, in relation to the time of diagnosis, 54.16% knew their serological status before prenatal care, 41.67% received the diagnosis during prenatal care and 4.17% during delivery. Regarding the use of antiretrovirals, 79.17% of the pregnant women used them during prenatal care and 79.17% of them during delivery, and the outcome of pregnancy in 87.50% of cases was a live birth. Conclusion: The study highlights the need to explore more factors that lead to HIV infection in pregnant women, in order to help monitor mother-to-child transmission and contribute to research aimed at the comprehensive protection of pregnant women and children.